PHYSICAL PLANNING APPROACHES OF TODAY'S CEMETERIES: KAYSERİ ASRİ CEMETERY CASE - Ahmet Moda; Banu Öztürk Kurtaslan (DEPARCH Journal of Design Planning and Aesthetics Research)
In this study, planning and design features of cemeteries were investigated by considering the development of cemetery concept in Turks and characteristics that determine the cemetery usage status and form were investigated. In the study, visitors' satisfaction degree of their visits to Kayseri Asri Cemetery in Kayseri City center which is continuing to grow have been examined. As a study area, Kayseri Asri Cemetery and the evaluation of the visitor satisfaction survey, firstly the compliance of the cemetery with the planning criteria was examined in general. The survey data of 384 people were analyzed with the help of SPSS Statistics program, and the data obtained were presented in graphical form. At the end of the research, some problems were determined in terms of design in parking lot, pedestrian and vehicle access, reinforcement elements, plant design in Kayseri Asri Cemetery. In addition, it is seen that the majority of the people of Kayseri do not want to spend time other than their use for visiting cemeteries. This situation was caused by the fact that the cemetery was not designed to include park and park-like areas and which may serve passive recreation.